Plasma Fibrin Degradation Products (Fdp ) In Patients With Pre Eclamptic Toxaemia (Pre-eclampsia) - Ahmed, Shaheda; Haque, Mahmudul; Alam, ASM Towhidul; Hossain, Kamal; Ahmed, Farhena; Tasnim, Nayeema (Journal of Chittagong Medical College Teachers’ Association, 2013)
Plasma fibrin degradation products (F.D.P.) assay measures the amount of fibrin split products in the blood. The high levels of F.D.P. in pre-eclampsia suggests that abnormal amount of degradation products are most likely due to localized lysis of fibrin in the uterine vascular compartment. The present case control study was designed to determine the relationship between plasma fibrin degradation products and pre-eclampsia. The study was carried out in the department of Biochemistry, Chittagong Medical College during the period of September 2011 to August 2012. The samples were collected from the department of Obstetrics and Gynecology, Chittagong Medical College Hospital, age from 18- 40 years. The data were collected by a structured questionnaire including age, socioeconomic condition, gravida, para, edema, blood pressure, proteinuria, history of hypertension, family history of pre-eclampsia and diabetes mellitus. Considering the cost of experiment and length of time, total 60 patients were included in this study. Among them 40 were considered as case (Blood Pressure > or = 140/90 mm of Hg and proteinuria > 0.3 gram/day) and 20 were considered as control (Blood Pressure < 140/90 mm of Hg and no proteinuria). Plasma fibrin degradation products were measured in all samples. Study showed that plasma FDP were more increased in pre-eclamptic patients than that of normal pregnancy (21.52 + 16.47 ugm/ml Vs 10.63 + 7.12 ugm/ml), P = <0.01. Result showed that percentage of raised plasma FDP is more in preeclamptic patients (100%) than that of normal pregnancy (75%), P= <0.01. Pearson's Correlation Coefficient (r) showed that there were positive correlation between blood pressure and plasma FDP (systolic blood plessure and plasma FDP, r=0.221,P=>.0.05 and diastolic blood pressure and plasma FDP, r=0.285,P=<0.05). Significantly raised level of plasma F.D.P. in pre-eclampsia help to formulate a management plan and thereby reduce the complications of this disease. JCMCTA 2013; 24 (1):9-13